2021
DOI: 10.1111/ppc.12910
|View full text |Cite
|
Sign up to set email alerts
|

Holistic nursing clinical practice experiences of nursing students in medical‐surgical clinics: A qualitative study

Abstract: Purpose: This study was conducted to examine the experiences of nursing students in holistic nursing clinical practice.Design: Twenty senior nursing students participated in this study. Data were collected through focus group interviews with a qualitative approach followed by thematic data analysis.Findings: Four themes were obtained holistic care, barriers to holistic care, the contributions of holistic nursing internship, and students' expectations.Practice Implications: The participants stated that they bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Students perceived that some factors, such as not having clinical experience, lacking knowledge and skills, and being in the role of a student regarding EoL care, were important challenges to caring for patients and their families. These perceptions match those presented in other studies exploring the perspectives of patients and their families or clinicians and/or students on barriers and motivators related to EoL care (Kaya et al, 2021; Luth & Pristavec, 2020, Su et al, 2021). In the study by Grubb and Arthur (2016), students reported that having experienced death and caring for patients during clinical practice, and having more education in EoL care were all associated with more positive attitudes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Students perceived that some factors, such as not having clinical experience, lacking knowledge and skills, and being in the role of a student regarding EoL care, were important challenges to caring for patients and their families. These perceptions match those presented in other studies exploring the perspectives of patients and their families or clinicians and/or students on barriers and motivators related to EoL care (Kaya et al, 2021; Luth & Pristavec, 2020, Su et al, 2021). In the study by Grubb and Arthur (2016), students reported that having experienced death and caring for patients during clinical practice, and having more education in EoL care were all associated with more positive attitudes.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, nursing students in other studies have described internal and/or external support as stimulating and rewarding, whereas deficient support was frustrating and made them feel helpless (Huang et al, 2010; Lian et al, 2019). The support and collaboration of healthcare team members during clinical practice are essential, especially given the multidimensional complexity and challenges of caring for patients in EoL (Kaya et al, 2021). Students may experience loss of professional interest, lack of motivation, apathy, anxiety, and fear if they encounter external barriers such as lack of support from instructors or colleagues, having poor role models, and experiencing negative attitudes from patients, families, or healthcare team members (Shafakhah et al, 2018; Su et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study investigating the supportive care needs of Western Australian women with gynaecological cancer found a need for ‘being treated like a person not just another case’ up to 57.3% (Williams et al, 2018). The shortage of nurses, lack of knowledge about holistic care, and lack of time have been reported as barriers to holistic care (Kaya et al, 2021). Several studies confirmed that holistic care benefits patients.…”
Section: Discussionmentioning
confidence: 99%
“…So the success of nursing services is largely determined by the performance of the nurses. Nurses are the largest group in the hospital organization who work 24 hours/day which makes them more highlighted than other health teams (Kaya et al, 2022). Coaching and development of nurses are the activities that must be carried out by the leadership/ head of the ward to support the performance of nurses.…”
Section: Introductionmentioning
confidence: 99%